A Method to Facilitate “Nonsticking” of Regular Bipolar Forceps - Huang, Hui-Kuang; Wang, Jung-Pan (Journal of Hand and Microsurgery, 2017)
Electrosurgery using a bipolar cautery is very common, especially in surgical fields with surrounding vital structures. However, the tissue tends to stick to the bipolar forceps due to the heat cautery, which makes the tips stick together. When forceps tips are stuck to the cauterized tissue, surgeons have to spend time separating the tips. Also, when surgeons separate the tips, a cauterized bleeder may rebleed. Some bipolar forceps with nonstick coatings have been developed to reduce the sticking problem. However, for some surgeons or institutes, these nonstick bipolar forceps may be unavailable. The authors describe an easy method to reduce the occurrence of sticking forceps tips if regular bipolar forceps are used.
Keywords: bipolar; cautery; electrosurgery; forceps; stick